Causes of death after surgery for colon cancer-impact of other diseases, urgent admittance, and gender. (1st October 2013) - Sjödahl, Rune; Rosell, Johan; Starkhammar, Hans
Abstract: Objective. In patients with colon cancer, high age and comorbidity is common. In this population-based retrospective study we have investigated causes of death and the influence of urgent operation, and gender on survival. Material and methods. Medical records of 413 patients with verified colon cancer were reviewed. The diagnosis was made during 2000–2006 and operation was performed in 385 patients (93%). Results. The overall 5-year survival after surgery was 48.3%. At the end of the follow-up, 128 patients (54.9%) had verified colon cancer when they died but 105 patients (45.1%) had no signs of colon cancer. Their 5-year survival was 5.5% and 41.9%, respectively ( p < 0.0001). Median survival time was significantly shorter after urgent compared with elective admittance, 20.7 months versus 77.9 months, and the 5-year survival 32.4% versus 57.9% ( p = 0.0001). The tumor stage at operation was more favorable in patients dying with no signs of colon cancer than in those dying with cancer regarding stage I–II (66.7% versus 16.4%), and stage IV (1.0% versus 53.1%), but not regarding stage III (30.5% versus 29.7%). The overall survival in women who were operated was longer than in men ( p = 0.045) as well as survival after elective admittance ( p = 0.013). Conclusion. After a median follow-up of 56.1 months almost half of the patients who were dead had died from other causes than colon cancer. Ten percent of those patients had an incorrectly reported diagnosis of colon cancer as cause of death. Urgent admittance was associated with reduced survival time. The median survival time was longer in women than in men.